Aktivitas antibakteri ekstrak metanol batang pisang mauli (Musa sp)terhadap Streptococcus mutans Antibacterial activity of methanol extract of mauli banana (Musa sp)stems against Streptococcus mutans - Maharani Laillyza Apriasari; Ahmad Fadhilah; Amy N. Carabelly (DiscoverSys Inc., 2013)
There are many traditional medicines that can be used as alternative medicine. One of them is methanol extract ofmauli banana stems. Some people in North of Hulu Sungai Banjarmasin use it as healing agent. The aim of thisresearch was to test antibacterial activity of mauli banana stems extract against Streptococcus mutans; as well as todetermine the effective concentration of its antibacterial activity against S.mutans. The extraction was conducted bymaceration method. Viscous extracts were diluted by using 10% dimethyl sulfoxide and filtered with Whatman paperfilter. Those extracts were divided into four treatment groups: 6.25% (I), 12.5% (II), 25% (III), and control (-)(IV).Groups I, II, and III were added with Muller Hinton media to reach the concentrations. 100 Î¼L S.mutans suspension of0.5 Mc Farland was administered to each concentration, incubated for 18 hours, diluted to 1/10 using NaCl. 100 Î¼Lwas taken and planted to blood agar media for 24 hours incubation. The numbers of S.mutans colonies were countedand statistically analysed by one-way anova test and post hoc LSD (p<0.05). The results showed that there weresignificant differences between each treatment, and extract concentration of 25% had better antibacterial activity thanthe others. It was concluded that extract of mauli banana steams have antibacterial activity against S.mutans, andmauli banana stem have the potential to be used as an alternative herbal mouthwash.